2013
DOI: 10.1371/journal.pone.0069530
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Guided Design of an Engineered Streptavidin with Reusability to Purify Streptavidin-Binding Peptide Tagged Proteins or Biotinylated Proteins

Abstract: Development of a high-affinity streptavidin-binding peptide (SBP) tag allows the tagged recombinant proteins to be affinity purified using the streptavidin matrix without the need of biotinylation. The major limitation of this powerful technology is the requirement to use biotin to elute the SBP-tagged proteins from the streptavidin matrix. Tight biotin binding by streptavidin essentially allows the matrix to be used only once. To address this problem, differences in interactions of biotin and SBP with strepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…Therefore, it can be applied to purify proteins tagged with either SBP, SBP(A18C) or biotin as well as other biotinylated molecules. Second, under optimized wash conditions, the new system does not show protein leakage in the wash fractions even when an affinity column is overloaded with the tagged protein, a problem previously observed in the SAVSBPM18-SBP system [ 13 ]. This newly developed system further advances the streptavidin-SBP technology to have the flexibility for both immobilization and reversible binding applications.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, it can be applied to purify proteins tagged with either SBP, SBP(A18C) or biotin as well as other biotinylated molecules. Second, under optimized wash conditions, the new system does not show protein leakage in the wash fractions even when an affinity column is overloaded with the tagged protein, a problem previously observed in the SAVSBPM18-SBP system [ 13 ]. This newly developed system further advances the streptavidin-SBP technology to have the flexibility for both immobilization and reversible binding applications.…”
Section: Introductionmentioning
confidence: 94%
“…The major drawback of this technology is that the affinity matrix can be used only once, since biotin is typically used as an effective competitor to elute SBP-tagged proteins from the matrix and the tight binding of biotin to streptavidin makes it impractical to remove biotin from the column. With the recent development of SAVSBPM18, an engineered form of streptavidin that can bind both SBP-tag and biotin with affinities in the range of 10 −8 M [ 13 ], we have shown that a SAVSBPM18-based affinity matrix can be used to purify either SBP-tagged or biotinylated biomolecules in a manner where the column can be easily regenerated and reused.…”
Section: Introductionmentioning
confidence: 99%
“…The recent discovery of a new streptavidin mutant that still maintains high-affinity binding to the SBP tag, but has significantly lower affinity for biotin so that the streptavidin matrix can be reused, may result in more frequent use of this novel tag on other proteins. 65 All of the tags discussed above can be engineered to be cleaved by site-specific proteases to remove the tags once purification is complete. 66 Tag removal is often desired for structural studies to prevent any tag-dependent artifacts, but it may also be important for screening campaigns that make use of reagents that bind to specific tags on targets.…”
Section: Fusion Tag Selectionmentioning
confidence: 99%
“…A number of affinity tags including enzymes, protein domains or small polypeptides has been developed (7). Of these, a streptavidin binding peptide (SBP)-based, 38 amino acids long tag, with high affinity to streptavidin (K D~2 .5×10 -9 M) enables a fast, efficient, and relatively specific one-step method for isolation and study protein complexes (8)(9)(10). Moreover, it provides better affinity, higher purity and higher yields over other commonly used tags like His tag or maltose binding protein and allows simple competitive elution by biotin under mild conditions (11) (biotin affinity to streptavidin is characterized by K D~1 ×10 -14 M) (9).…”
mentioning
confidence: 99%
“…Of these, a streptavidin binding peptide (SBP)-based, 38 amino acids long tag, with high affinity to streptavidin (K D~2 .5×10 -9 M) enables a fast, efficient, and relatively specific one-step method for isolation and study protein complexes (8)(9)(10). Moreover, it provides better affinity, higher purity and higher yields over other commonly used tags like His tag or maltose binding protein and allows simple competitive elution by biotin under mild conditions (11) (biotin affinity to streptavidin is characterized by K D~1 ×10 -14 M) (9). In a practical set-up, every pull-down assay comprises five main steps: i) cell lysis, ii) capture of tagged protein onto solid support and wash off unspecific interacting biomolecules, iii) elution of specific interaction partners, iv) protein digestion and v) mass spectrometry (MS) identification and quantification of interacting partners in comparison with the control assay ( Figure 1).…”
mentioning
confidence: 99%